Determining the effective mode of operation for the system of washing the milking machine milk supply line - Paliy, Andriy; Aliiev, Elchyn; Paliy, Anatoliy; Kotko, Yana; Kolinchuk, Ruslan; Livoschenko, Evgenia; Chekan, Oleksandr; Nazarenko, Svitlana; Livoschenko, Ludmila; Uskova, Liliya (Eastern-European Journal of Enterprise Technologies, 2022)
The application of techniques for effective cleaning of milking routes in milking machines is an important way to improve the quality of milk and increase labor productivity in dairy farming. The object of research was the system of washing the milk line of the milking machine with the upper milk line. The problem of rational use of energy resources was solved in the implementation of a routine operation – washing the milking machine. Experimental studies were carried out according to the Box-Benkin plan of the second order for 3 factors (the speed of movement of the washing solution, V; the temperature of the washing solution, T; the duration of the rinsing phase, t). In this case, a mathematical apparatus for planning a multivariate experiment according to the D-optimal plan was used. It was found that with an increase in the speed of movement of the washing solution and temperature, as well as the duration of the rinsing phase, the number of microorganisms on the surfaces of the nodes and elements of the milky line decreases. Milk lines of the milking machine made of any material are better cleaned with a hotter washing solution (40 °C) than with a cold one (20 °C). Thus, when cleaning with a solution of 40 °C of stainless steel and food aluminum, the reduction of microorganisms is 4.3 times, glass – 4 times, and rubber – 4.7. The essence of the experiment was to establish patterns when cleaning the milk line from various materials. The influence of the regime parameters (the speed of movement of the washing solution, V; its temperature, T; and the duration of the rinsing phase, t) on the energy consumption of the milking machine, E, was determined. The compromise problem of rationalizing the washing modes of the milk lines of the milking machine has been solved. Thus, rational mode parameters for the washing system were established: V=2.4 m/s, T=38.2 °C, t=3.2 minutes. With these parameters, the optimization criteria are: N=79 thousand CFU/cm3, Q=23.3 l, E=8.08 kWh